The use of the Risk Assessment and Prediction Tool in surgical patients in a bundled payment program. (February 2017) - Slover, James; Mullaly, Kathleen; Karia, Raj; Bendo, John; Ursomanno, Patricia; Galloway, Aubrey; Iorio, Richard; Bosco, Joseph
Abstract: Objectives: The purpose of this study was to evaluate the relationship between the Risk Assessment and Predictor Tool (RAPT) and patient discharge disposition in an institution participating in bundled payment program for total joint replacement, spine fusion and cardiac valve surgery patients. Method: Between April 2014 and April 2015, RAPT scores of 767 patients (535 primary unilateral total joint arthroplasty; 150 cardiac valve replacement; 82 spinal fusions) were prospectively captured. Total RAPT scores were grouped into three levels for risk of complications: <6 = 'high risk', between 6 and 9 = 'medium risk', and >9 = 'low risk' for discharge to a post-acute facility. Associations between RAPT categories and patient discharge to home versus any facility were conducted. Multivariate analysis was performed to determine if there was any correlation between RAPT score and discharge to any facility. Results: 70.5% of total joint patients, 80.7% of cardiac valve surgery patients and 70.7% of spine surgery patients were discharged home rather than to a post-acute facility. RAPT risk categories were related to discharge disposition as 72% of those in the high risk group were discharged to a facility and 91% in the low risk group were discharged to home in the total joint replacement cohort. In the cardiac cohort, only 33% of the high risk group was discharged to a facility, and 94% of the low risk group was discharged to home. In the spinal fusion cohort, 60% of those in the high risk group were discharged to a facility and 86% in the low risk group were discharged to home. Multivariate analysis showed that being in the high risk category versus low risk category was significantly associated with substantially increased odds of discharge to a facility. Conclusion: The RAPT tool has shown the ability to predict discharge disposition for total joint and spine surgery patients, but not cardiac valve surgery patients, where the majority of patients in all categories were discharged home, at an institution participating in a bundled payment program. The ability to identify discharge disposition pre-operatively is valuable for improving care coordination, directing care resources and establishing and maintaining patient and family expectations. Highlights: RAPT predict discharge disposition for total joint and spine surgery patients, but not cardiac valve surgery patients, in a bundled payment program. RAPT is valuable for improving care coordination, directing care resources and establishing and maintaining patient and family expectations.